Exploring the therapeutic potential of cannabinoids in cancer by modulating signaling pathways and addressing clinical challenges - Faiz, Manal Bint; Naeem, Faiza; Irfan, Muhammad; Aslam, Muhammad Adeel; Estevinho, Leticia M.; Atessahin, Dilek Arslan; Sharifi-Rad, Javad (Springer, 2024)
For centuries, cannabinoids have been utilized for their medicinal properties, particularly in Asian and South-Asian countries. Cannabis plants, known for their psychoactive and non-psychoactive potential, were historically used for spiritual and remedial healing. However, as cannabis became predominantly a recreational drug, it faced prohibition. Recently, the therapeutic potential of cannabinoids has sparked renewed research interest, extending their use to various medical conditions, including cancer. This review aims to highlight current data on the involvement of cannabinoids in cancer signaling pathways, emphasizing their potential in cancer therapy and the need for further investigation into the underlying mechanisms. A comprehensive literature review was conducted using databases such as PubMed/MedLine, Google Scholar, Web of Science, Scopus, and Embase. The search focused on peer-reviewed articles, review articles, and clinical trials discussing the anticancer properties of cannabinoids. Inclusion criteria included studies in English on the mechanisms of action and clinical efficacy of cannabinoids in cancer. Cannabinoids, including Delta 9-THC, CBD, and CBG, exhibit significant anticancer activities such as apoptosis induction, autophagy stimulation, cell cycle arrest, anti-proliferation, anti-angiogenesis, and metastasis inhibition. Clinical trials have demonstrated cannabinoids' efficacy in tumor regression and health improvement in palliative care. However, challenges such as variability in cannabinoid composition, psychoactive effects, regulatory barriers, and lack of standardized dosing remain. Cannabinoids show promising potential as anticancer agents through various mechanisms. Further large-scale, randomized controlled trials are essential to validate these findings and establish standardized therapeutic protocols. Future research should focus on elucidating detailed mechanisms, optimizing dosing, and exploring cannabinoids as primary chemotherapeutic agents.
Keywords: Anticancer effects; Apoptosis; Cannabinoids; CBD; Delta 9-THC; Metastasis; Pharmacological mechanisms